Integrating the technology acceptance model for social media-based learning with authentic leadership development: symmetric and asymmetric modeling - Asghar, Muhammad Zaheer; Rasool, Samma Faiz; Seitamaa-Hakkarainen, Pirita; Arif, Seema; Bano, Sumaira (Frontiers in Psychology, 2023)
The growing trend of social media use has influenced all segments of society. This study focused on the use of social media-based learning for authentic leadership development among preservice teachers. We conducted a needs analysis survey to measure preservice teachers' intentions towards social mediabased learning using the technology acceptance model (TAM). The needs analysis survey showed that preservice teachers have a positive intention towards social media-based learning. Based on our recommendations, the teacher education department launched courses through social media during the pandemic lockdown. Authentic leadership is considered an emerging concept in positive psychology for dealing with emergency situations in the dot com era. We conducted a second survey to measure the influence of social media-based learning on the authentic leadership development of preservice teachers. The results revealed that social media-based learning enhanced preservice teachers' authentic leadership characteristics, such as ethics, self-regulation, and self-awareness. This study is among the pioneering studies to integrate TAM (i.e., acceptance of social media-based learning) with leadership theory (i.e., authentic leadership). It also adds a methodological contribution by combining both symmetrical (i.e., Partial Least Squares Structural Equation Model) and asymmetrical (i.e., Fuzzy Set Comparative Qualitative Analysis) data analysis approaches. The study's findings are valuable for teacher education institutions, as they help prepare future teachers to become authentic leaders capable of addressing future crises by leveraging education through social media-based learning.